Governança da educação pública em Maceió: uma análise do programa Viva Escola (2013-2018) - Braz, Elainy Paula Viturino (2019)
Since 2013, the educational policy of the city of Maceió has been reformulated by the actions of the Viva Escola Program, a partnership between the United Nations Development Program (UNDP), the Maceió Municipal Education Department (SEMED) and the Ministry of Education (MEC). Together with MEC, this program is linked to Project MEC / UNDP No. 77150/2011. This partnership, which demonstrates the closer relationship between the city government of Maceió and UNDP, aims to ensure minimum operating and quality parameters for the municipal school system, aiming to establish governance processes and mechanisms through reforms in educational policies. Therefore, the study questions were as follows: how have the actions of the Viva Escola Program contributed to the construction of governance of education in the city of Maceió? In what ways has the city's educational policy been guided by UNDP's political agenda? What changes reveal strategies for reaching society's active consent to the ongoing educational reform in education management? The research, with qualitative approach, was guided by the dialectical method. The general objective of the research was to analyze the construction of the governance of education in the city of Maceió through the partnership between UNDP and SEMED, materialized in the Live School Program, seeking to elucidate the strategies of achieving active consent on the ongoing educational reform. in education management. Based on literature review and bibliographic survey, the methodological procedures included document analysis and semi-structured interviews with 2 (two) UNDP subjects directly involved in the Viva Escola Program. The documentary analysis dealt with educational policy documents resulting from the SEMED / UNDP partnership and the Live School Program. Content analysis was the technique used for the treatment of interviews. The main conclusions of the study were as follows: the governance of the Maceió municipal public school education has been built by the actions of the SEMED / UNDP partnership, through actions linked to the Viva Escola Program, which synthesizes the educational policy of the municipality. These partners are the main actors in the formulation of educational policy, in line with the global education project represented by the 2030 Agenda. Effective governance of education were as follows: drafting educational policy documents in a participatory manner; expansion of actions of Viva Escola's partner network to improve the quality of education; involvement of municipal network professionals in the governance of education. These elements were relevant for the insertion of governance mechanisms in the education network and for reaching new partners that reinforce the global education project to which the Viva Escola Program is linked.